Digitalization and Public Service Efficiency: Evidence from Registry and Notary Administration in Timor-Leste - João dos Santos; Leoneto M. Martins; João M. dos C. Noronha (Journal of Political Innovation and Analysis, 2026)
Digitalization has become a strategic priority in public administration reform, particularly in improving the efficiency and effectiveness of service delivery in developing countries. In Timor-Leste, civil registry and notary services have traditionally relied on manual processes, resulting in delays, administrative inefficiencies, and limited data integration. This study aims to examine the impact of digitalization through the implementation of the Digital Management Information System (DMIS) 4.0 at the Municipal Directorate of Civil Registry and Notary Services in Dili. This research employs a qualitative analytical approach, using observation, in-depth interviews with six key informants, and document analysis. Data were analyzed using thematic analysis to identify patterns related to efficiency, effectiveness, and implementation challenges. The findings reveal that the implementation of DMIS 4.0 significantly improves service efficiency by reducing processing time, minimizing administrative errors, and streamlining workflows. At the same time, service effectiveness is enhanced through improved data accuracy, accessibility, and integration across administrative units. However, the study also identifies key challenges, including limited technological infrastructure, unstable internet connectivity, and varying levels of digital literacy among employees, which affect system performance. This study concludes that digitalization functions as a socio-technical transformation requiring alignment between technology, human resource capacity, and institutional readiness. The findings contribute to the limited empirical literature on digital governance in small developing countries and provide practical insights for strengthening digital public service systems.